A Simplified Review of Cloud Computing in the Healthcare System - Atin Bera; Arya Bhattacharyya; Radhakrishna Jan; Sudipta Kumar Dutta (International Journal of Computer Sciences and Engineering, 2023)
One of the key drivers of the health information revolution in the healthcare industry is cloud computing. Cloud computing makes it possible for anyone to exchange digitized health records globally. This technology fosters innovation and enhances safety in the healthcare industry. The use of this technology makes communication with the health matrix possible on a global scale. For many years, cloud computing has been used in the healthcare industry and has developed along with changes in the business. Through a network connection, this technology creates universally usable hardware for a range of healthcare applications. Doctors can provide their patients with health advice and communicate their daily health routines, often maintaining the health of their bodies and brains. By using videoconferencing, psychologists and psychiatrists may create a pleasant environment for their patients. The necessity for cloud computing in healthcare is covered in this essay. The large key is that the benefits, drawbacks, and difficulties of cloud computing for the healthcare sector are noted. Finally, it discusses the important uses of cloud computing in the field of healthcare. Increasingly, healthcare providers are giving Internet of Things (IoT)-equipped devices to patients, and by connecting these devices to the cloud systems of hospitals, patient data is promptly sent to their physicians. Because of this, cloud computing enhances efficiency and multiplies the methods for streamlining healthcare delivery. These fast-evolving technologies include Big Data analytics, artificial intelligence, and the Internet of Medical Things. It increases interoperability, increases resource availability, and lowers costs.